Manakala Konflik Berkepanjangan Harus Diselesaikan: Kasus Konflik Perkebunan Ketajek, Jember - Aprianto, Tri Chandra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2009)
For years there has not been any rigid formula for land conflict resolution in Indonesia. Structurally, the conflicts occur as the result of the centralistic-based management of the land-ownership. As such method is still being retained in reformasi era, thus the conflicts remain continue untill now particularly in some part of Indonesia. This paper discuss the claim of land rights in Perkebunan Ketajek in Jember, East Java. It also tries to offer the most possible solution for the more fair land management system. The claim of land rights itself is not just about the land ownership disputes. Moreover it is about the land system of which the social values are preserved within the society.